Thermal and mechanical assessments of the 3D-printed conformal cooling channels : computational analysis and multi-objective optimization - Shen, Suping (2021)
Conformal cooling is an additive manufacturing-based solution and it is a rapidly developing method for reducing the cooling time of the plastic injection process. The present study investigates the thermal and mechanical performances of the 3D-printed conformal cooling channels using computational analyses and multi-objective optimization. For a real injection mold product, two different conformal cooling channel profiles, which are circular and elongated, are analyzed individually. Their cooling time, temperature non-uniformity, and pressure drop are assessed. Compared to the traditional channels, the cooling time of designed CCCs is reduced in the range of 30-60%. The cooling and fatigue life performances of the elongated channel are analyzed for different channel pathways and cross section areas. As for the circular channel, the coolant temperature, volume flow rate, and channel diameter are selected as the parameters within the ranges of 288.0-298.0 K, 1.0-10.0 L/min, and 2.1-2.5 mm, respectively. According to these parameters, the multi-objective optimization study is performed and the best trade-off point is found at the channel diameter of 2.5 mm, coolant temperature of 297 K, and the flow rate of 1 L/min when all the objectives have equal weights in the optimization problem.